Pengaruh Brand Equity Terhadap Brand Loyalty pada Produk Skincare Serum yang Dimediasi oleh Customer Satisfaction - Febrianto, Rachel Yuki Ellycia; Fajarwati, Diana (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
The aim of this research is to explore the influence of Brand Equity on Brand Loyalty for Skincare Serum Products Mediated by Customer Satisfaction and to confirm the significant dimensions of Brand Equity. The population of this study is unknown number of Skincare Serum users domiciled throughout Indonesia. The respondents for this research were 150 respondents with the criteria of Skincare Serum users aged 17 – 50 years who had purchased and used Skincare Serum in the last 6 months. The analytical method used is Partial Least Square Structural Equation Modeling. The results of the research state that Perceived Quality and Perceived Cost Value can increase Customer Satisfaction and have a positive effect on Brand Loyalty, however Brand Identification, Brand Trust and Lifestyle Congruence have no effect on Customer Satisfaction. Perceived Quality and Perceived Cost Value on Brand Loyalty are mediated by Customer Satisfaction, while Brand Identification, Brand Trust and Lifestyle Congruence are not proven